Spatial variability of soil organic carbon stock in an olive orchard at catchment scale in Southern Spain - Gómez, Jose A.; Guzmán, Gema; Vanwalleghem, Tom; Vanderlinden, Karl (International Soil and Water Conservation Research, 2023)
Orchards have a high potential for carbon sequestration. However, little research is available on the spatial variability at catchment scale and on the difference between the tree area and the lanes. We analyzed theik spatial variability of soil organic carbon stock, SOCstock at 90 cm depth in an 8-ha catchment in Southern Spain with olives on a vertic soil. Results showed higher soil organic carbon concentration, SOC, in the tree area as compared to the lane up to 60 cm depth, but its impact on SOCstock was negligible since it was compensated by the higher soil bulk density in the lane. SOC at different depths was correlated with that in the top 0–5 cm. The overall SOCstock of the orchard was 4.14 kg m−2, ranging between 1.8 and 6.0 kg m−2. This SOCstock is in the mid-lower range of values reported for olive orchards, measured at smaller scale, and similar to those other intensive field crops and agroforestry under comparable rainfall conditions. The spatial variability in SOCstock was correlated to several geomorphological variables: elevation, cumulative upstream area, topographic wetness index, sediment transport index, and tillage erosion. Differences in SOC and SOCstock are driven by the sediment redistribution downslope, mainly by tillage erosion, and higher soil water availability in lower areas allowing higher biomass production. These topographic indexes and the correlation between SOC in the topsoil and SOCstock up to 90 cm should be further explored in other typology of olive orchards for facilitating the mapping of SOCstock.